Sport Tourism in Eastern Economic Corridor - Saorong, Pattarawadee (Journal of Education Rajabhat Maha Sarakham University, 2020)
The purposes of this research were 1) to study and explore sports tourism resources and sports tourism situation in Rayong province and 2) Presenting a value creation model by sports tourism for Rayong province. Collect data from literature review. Quantitative data obtained from 400 tourists by accidental sampling by using a questionnaires. Qualitative data based on in–depth interviews with 5 experts by random sampling by using an interview forms. Assessing the suitability and feasibility of the model by group discussions from experts in economics, tourism and sport, 7 persons. The result revealed that 1) Sports tourism resources and situations in Rayong province, found that Rayong province is well equipped to manage sports tourism at a good level in all 7 aspects, 2) The model of creating value added by sports tourism for tourism development in Rayong province consists of policies, development plans and sports tourism situations of the province. Management and marketing processes with success factors: (1) Choosing the right sport type, (2) Joint venture with the private sector, (3) Building awareness and participation of local people and 4) Making travel and sports calendars to have consistency. The findings from this research Rayong province can be considered to be implemented in order to form practices to create benefits for sports tourism development Bring more revenue and economic value.